Effects of land-use change on Nitisols properties in a tropical climate - Viciedo, Dilier Olivera [UNESP]; Hernández, Alberto; Rodríguez, Manuel; Lizcano, Rodolfo; Calero, Alexander [UNESP]; Peña, Kolima [UNESP] (Universidad Nacional de Colombia, 2018)
Land use change, especially conversion of native forests to cultivated land, exerts an impact on the physical, chemical and hydrophysical soils properties. To quantify and better understand responses, this study was aimed at evaluating the influence of different tropical soil management systems reflected in some physic, chemical and hydro-physical properties. Nine Nitisol profiles were evaluated and grouped in three categories: (I) native forest (Benchmark > 30 years); (II) soils formerly cultivated then turned to pasture (Conservation > 10 years); and (III) soils under continuous cultivation (Agrogenic > 50 years). The analyzed variables were organic matter, bulk density, soil particle density, porosity, field capacity, texture and structural index. Results determine that the action of traditional farming techniques in tropical environments produces excessive soil degradation. Organic matter content and the structural index showed a linear relationship with high degree of dependence (R2=0.99). Bulk density average for (I) and (II) profile were lower (P<0.05) than the bulk density values for (III). In the regression analyses the bulk density increased, the field capacity decreased, and the tendency for profile (I) and (II) were of a linear type. While the profile for (III) was of a polynomial type with (R2=0.83), being able to be influenced by the higher values of bulk density, greater soil compaction, lower structural index, organic matter and porosity in correspondence with the other profiles.
Efectos del cambio de uso de la tierra en las propiedades de los Nitisoles en un clima tropical
Keywords: Degradation; Physical properties; Soil management; Tillage